An Exploration of Unani Concept of Pain with Conventional Medicine - Sana Kauser Ahmed; Sanila Zafar; Tasfiya Ansari (Journal of Research on History of Medicine, 2023)
The intention of medicine is to retain and restore health and relieve suffering. Understanding pain is essential to achieving any one of these goals. It is irrefutable that every individual experiences pain in their life and is one of the commonest manifestations a physician encounters in their career. Pain makes sufferers and physicians aware of the presence of some disorders. This is the primary steps for the physician to protect the body from diseases and restore health. In addition, there is a close relationship between pain and psychological state. Pain can arise either as a consequence of physical problem or because of a psychological process. Aristotle, who associated pain with sensation, observed that where there is a sensation, there is pleasure and pain too. In addition, apparently, he regarded pain as a qualifying sensation. Relevant literary material for this paper was collected from classical Unani literature as well as modern medicine. Then, available literary material was analysed and organized systematically. This review article aims to provide a breeding ground for reflection on the concept of pain according to the Unani system of medicine and to encourage the identification of a meaningful aspect of this complex condition.